A Case of Misdiagnosed Cesarean Scar Pregnancy with a Viable Birth at 28 Weeks - Sakiko Nukaga; Shigeru Aoki; Kentaro Kurasawa; Tsuneo Takahashi; Fumiki Hirahara (Case Reports in Obstetrics and Gynecology)
We report our experience with a case of presumptive cesarean scar pregnancy, based on detection of a gestational sac (GS) in early pregnancy at the site of a previous cesarean scar. The GS grew into the uterine cavity as the pregnancy progressed, showing an ultrasound image similar to that of a normal pregnancy. Thus, the pregnancy continued, resulting in a viable birth at 28 weeks of gestation. Cesarean scar pregnancy is classified as myometrial implantation or implantation growth into the uterine cavity. In the latter type, the gestational sac moves upward with increasing gestational weeks and it shows the same ultrasound image as a normal pregnancy. Therefore, the diagnosis must be made in the early pregnancy.